PRODUÇÃO IN VITRO DE EMBRIÕES BOVINOS EM MEIO SUPLEMENTADO COM FONTES PROTÉICAS DEFINIDAS E INDEFINIDAS - MOZZAQUATRO, F.D.; RUBIN, M.I.B.; SILVA, C.A.M.; TESSMANN, J.V.; RAUBER, L.P.; KURTZ FILHO, M.; SCHERER, D.; BUNN, S. (Archives of Veterinary Science, 2004)
Quinhentos e trinta e três (n=533) complexos cumulus-oócitos (CCO) bovinos foram utilizados para comparar a suplementação dos meios de maturação e cultivo com diferentes fontes protéicas: soro de égua em estro (SEE; n=150) e soro de vaca em estro (SVE; n=123), álcool polivinílico (PVA; n=128) e albumina sérica bovina (BSA; n=132). Os grupos de CCO foram distribuídos aletoriamente e maturados in vitro por 24h em TCM199 com 10% de SEE, 10% SVE, 0,1% PVA e 0,6% BSA em estufa de cultivo com 5% de CO2, a 39ºC e umidade saturada. A fecundação foi realizada durante 18h, em meio FERT-TALP em estufa de cultivo. Os embriões foram cultivados por 8 dias em meio synthetic oviduct fluid (SOFaaci) com 5% SEE, 5% SVE, 0,1% PVA e 0,6% BSA em estufa de cultivo a 39ºC, sendo mantidos em bolsas gaseificadas com 5% CO2, 5% O2 e 90% N2. A produção de embriões no D7 nos tratamentos SEE (33/142; 23%) e SVE (34/103; 33%) foi superior (P<0,05) a dos tratamentos PVA (6/116; 5%) e BSA (4/126; 3%). No D9, a taxa de blastocistos nos tratamentos SEE (22/142; 15%) e SVE (22/103; 21%) foram superiores (P<0,05) a do grupo BSA (3/126; 2%). A produção de blastocistos foi superior quando se adicionou soro ao meio de cultivo. Confirmou-se neste estudo que o SEE é uma alternativa para a PIV por três importantes razões: as taxas de produção embrionária obtidas, a facilidade de processamento e a redução da possibilidade de transmissão de doenças espécie-específicas. In vitro production of bovine embryos in medium supplemented with defined and undefined protein sources Abstract Five hundred and thirty three (n=533) bovine cumulus-oocytes complexes (COC) obtained by aspiration of 2-8mm diameter follicles were used to compare maturation and culture media containing distinct protein sources: estrus mare serum (EMS; n=150), estrus cow serum (ECS=123), polyvinyl alcohol (PVA; n= 128) and bovine serum albumin (BSA; n=132). COC groups were randomly distributed into treatments and in vitro maturated (IVM) in TCM-199 + 10% EMS, 10% ECS, 0.1% PVA and 0.6% BSA for 24h using an incubator with 5% CO2 at 39ºC and saturated air humidity. Fertilization was accomplished during 18h in FERT-TALP medium at the same temperature and gas atmosphere of the previous maturation phase. Denudation was performed and the zygotes were cultured for 8 days in synthetic oviduct fluid (SOFaaci) medium + 5% EMS, 5% ECS, 0.1% PVA and 0.6% BSA in an incubator at 39ºC using gasified bags with 5% CO2, 5% O2 and 90% N2. Embryo production in D7 for treatments EMS (33/142; 23%) and ECS (34/103; 33%) were higher (P<0,05) than PVA (6/116; 5%) and BSA (4/126; 3%). On day 9 blastocysts development rates in EMS (22/142; 15%) and ECS (22/103; 21%) treatments were higher (P<0.05) than in BSA (3/126; 2%). Blastocyst production was higher with the addition of serum to the medium. It was confirmed that EMS is an alternative for in vitro production (IVP) for three important reasons: the embryo production rates obtained, the easiness of the process and the reduction of the possibility of specific species disease transmission.